Meritorious Academic Partnership Designation: Recognizing Nursing Professional Development in Graduate Curricula. Issue 5 (September 2019) - Harper, Mary G.; Burke, Kathleen G.; Keim, Susan K.; Morgan, Larissa; Maloney, Patsy
Abstract : Graduate nursing education programs' focus on preparation for academia results in many graduate nurses being unprepared to function as nursing professional development (NPD) practitioners in the practice environment. This article describes the development of an innovative collaborative partnership designation program and how a specialty organization, health system, and academia partnered to create an educational program to prepare NPD practitioners. The designation program provides a practical tool for use by NPD departments to advocate for the NPD specialty.